Effect of solvent gradient on DNA confined in a strip - Mohanta D.; Giri D.; Kumar S. (My University, 2025)
We consider a double-stranded DNA (dsDNA) confined between two walls of a strip of finite width. We investigate the effect of solvent gradient on the transfer of dsDNA from one wall to the other. For this a mutually self-attracting self-avoiding walk model of polymer has been considered on the square lattice. The strength of base-pairing interactions between the two strands across the strip has been varied to model the solvent gradient. Using the exact enumeration technique we explored the effect of sequence and solvent gradient on the melting profile of short chain DNA. These results are substantiated by Monte Carlo simulations for a longer chain. The simple model presented here captures essential physics of transport in the biological processes. © 2020 Elsevier B.V.